Deadlock detection in distributed system - Kshirod Kumar Rout; Debani Prasad Mishra; Surender Reddy Salkuti (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In highly automated devices, deadlock is a case that occurs when no system can permit its event which may give irrelevant economic losses. A process can request or release resources that are either available or are on hold by others. If a process requesting a resource is not available at any time, then that process enters into the waiting state. But if a waiting state is not converted into its present state, it enters more than two processes are having an indefinite waiting state. The proposed algorithm gives an efficient way for deadlock detection. For the implementation of this work, C++ and python as the basic programming language are used. It gives an idea about how resources are allocated, and how few processes result in deadlock.